The Influence OF THE TEAM GAMES TOURNAMENT (TGT) MODEL ACCOMPANIED BY MIX AND MATCH MEDIA ON THE INTERESTS AND COGNITIVE LEARNING OUTCOMES OF STUDENTS OF DIFFERENT GENDERS AT IHSANUL FIKRI MUNGKID HIGH SCHOOL ON HUMAN REPRODUCTIVE SYSTEM MATERIAL. - Purwati, Elisyazahrayonawati (Bio-Lectura : Jurnal Pendidikan Biologi, 2024)
This study investigated the effect of the Team Games Tournament (TGT) model with mix and match media on cognitive learning outcomes and interest in human reproduction among students of different genders at SMA IT Ihsanul Fikri Mungkid. Quantitative methods with a quasi-experimental design with a non-equivalent control group was employed. The sample consisted of class XI male and female students, with the fourth class totaling 144 students as the experimental class and control class. Results showed no significant difference in cognitive learning outcomes and interest between the TGT model with mix and match media and traditional methods across genders, although the experimental group had a higher average score than the control group. the results of the final percentage of interest for the experiment and control women were 44% very high and 54% moderate. Final interest in experimental and control men was 61% very high and 44% moderate. The study concludes that the TGT model with mix and match media does not significantly influence cognitive learning outcomes and interest in human reproduction among students of different genders at SMA IT Ihsanul Fikri Mungkid.